Impact of insecticide resistance on the field control of Aedes aegypti in the State of São Paulo - Macoris, Maria de Lourdes da Graça; Andrighetti, Maria Teresa Macoris; Wanderley, Dalva Marli Valério; Ribolla, Paulo Eduardo Martins [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2014)
Introduction The need to control dengue transmission by means of insecticides has led to the development of resistance to most of the products used worldwide against mosquitoes. In the State of São Paulo, the Superintendência de Controle de Endemias (SUCEN) has annually monitored the susceptibility of Aedes aegypti to insecticides since 1996; since 1999, surveys were conducted in collaboration with the National Network of Laboratories (MoReNAa Network) and were coordinated by the Ministry of Health. In this study, in addition to the biological characterization of insecticide resistance in the laboratory, the impact of resistance on field control was evaluated for vector populations that showed resistance in laboratory assays. Methods Field efficacy tests with larvicides and adulticides were performed over a 13-year period, using World Health Organization protocols. Results Data from the field tests showed a reduction in the residual effect of temephos on populations with a resistance ratio of 3. For adults, field control was less effective in populations characterized as resistant in laboratory qualitative assays, and this was confirmed using qualitative assays and field evaluation. Conclusions Our results indicated that management of resistance development needs to be adopted when insect populations show reduced susceptibility. The use of insecticides is a self-limiting tool that needs to be applied cautiously, and dengue control requires more sustainable strategies.
Keywords: Aedes aegypti control; Field control; Insecticide resistance